FLIGHT SAFETY IMPROVED BY HANDLING OF WILDLIFE HAZARD - Putri Lestari, Nuraini; Hariyanto, Didi; Olieve, Arnaz (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2023)
Indonesia is one of the countries that has many islands so that people need transportation, especially aircraft as a support for increasing mobility. There is a wildlife hazard and birdstrike is one of the factors that can endanger flight safety. This type of research is descriptive qualitative with the aim of this study to determine the efforts made in handling and preventing wildlife hazards, knowing the solutions in efforts to handle wildlife hazards, and knowing how effective the solution is in handling wildlife hazards at Kualanamu International Airport Medan. The problem that the author puts forward in this research is the handling of wildlife hazards, the prevention of wildlife hazards, and the effectiveness of handling wildlife hazards at Kualanamu International Airport Medan. The research method that the author uses is by means of data collection techniques through the process of observation, documentation, interviews, and literature studies. The data analysis technique used in this research is data reduction, namely focusing on important things, presenting data in the form of a brief description containing charts and flowcharts, and drawing conclusions. The result of this research is to carry out handling and expulsion of wildlife hazard and birdstrike in the airside area to be more careful in carrying out monitoring, calculation, and expulsion in order to minimize the occurrence of unwanted incidents.